Thermogravimetric analysis of high-density cork granules using isoconversional methods - Ribeiro, A.M. (2022)
In the present work thermogravimetric techniques were used to study the thermal degradation of high-density cork granules. Pyrolysis experiments were carried out for four heating ramps (10, 15, 20 and 25 °C.min−1), using nitrogen as the carrier gas. From the differential thermogravimetric (DTG) curves it was seen that degradation mainly occurs from 220 °C to 525 °C for the main components of cork (suberin, lignin, cellulose, and hemicellulose). It was also observed that for temperatures higher than 525 °C and up to 900 °C, lignin continued to decompose. Activation energies were calculated using the data obtained and the two isoconversional methods Kissinger–Akahira–Sunose (KAS) and Flynn–Wall–Ozawa (FWO). For the KAS method, and for degrees of conversion between 0.10 and 0.85, the activation energies varied between 232.2 and 353.0 kJ.mol−1. Using the FWO method and for the same degrees of conversion, the activation energies were in the range of 230.0 to 346.6 kJ.mol−1. These values agree with data provided by other authors, for different lignocellulosic biomass.